2022
DOI: 10.3390/biom12121816
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Membrane Affinity and Binding Modes in Alpha-Synuclein Regulation of Vesicle Release and Trafficking

Abstract: Alpha-synuclein is a presynaptic protein linked to Parkinson’s disease with a poorly characterized physiological role in regulating the synaptic vesicle cycle. Using RBL-2H3 cells as a model system, we earlier reported that wild-type alpha-synuclein can act as both an inhibitor and a potentiator of stimulated exocytosis in a concentration-dependent manner. The inhibitory function is constitutive and depends on membrane binding by the helix-2 region of the lipid-binding domain, while potentiation becomes appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 91 publications
1
10
0
Order By: Relevance
“…Two α -synuclein mutants with high α -helix content were also predicted. Although the authors did not provide an exact secondary structure content, their study postulated that mutant 3AE has a higher α -helix content than mutant 4G [8]. Our model predicts 59.3% for the α -helix content of the 3AE mutant and 37.8% for the α -helix content of the 4G mutant, consistent with the authors’ study results.…”
Section: Discussionsupporting
confidence: 90%
“…Two α -synuclein mutants with high α -helix content were also predicted. Although the authors did not provide an exact secondary structure content, their study postulated that mutant 3AE has a higher α -helix content than mutant 4G [8]. Our model predicts 59.3% for the α -helix content of the 3AE mutant and 37.8% for the α -helix content of the 4G mutant, consistent with the authors’ study results.…”
Section: Discussionsupporting
confidence: 90%
“…We found previously that proline point mutations within either helix-1 (A30P) or helix-2 (V70P) locally disrupt the helical structure as determined by NMR measurements, and also disrupt membrane binding (A30P, V70P) or tethering (V70P) capacity of a-syn, as measured with liposome/micelle binding in vitro and stimulated exocytosis of recycling endosomes in cells. 1,31 The stimulated mitochondrial uptake assay showed that both mutations significantly attenuate the enhancing effect of Wt-syn: Control empty vector (20%) ≈ V70P-syn (20%) < A30Psyn (30%) << Wt-syn (75%) (Figure 2a). This trend in functional effects correlates with previously observed effects of these mutations on a-syn localization to mitochondria: Wt-syn co-localizes with mitochondria much more strongly than A30P-syn, and V70P-syn co-localization is undetectable.…”
Section: Resultsmentioning
confidence: 99%
“…21,56,58 Our previous NMR measurements showed that proline point mutations A30P within helix-1 and V70P within helix-2 locally disrupt the helical structure of the protein 1 , while also reducing the overall affinity of the protein for membranes. 31 These perturbations have functional consequences. For example, we showed previously that whereas Wt-syn inhibits stimulated exocytosis of recycling endosomes, V70P-syn abrogates this effect, evidently by preventing a-syn bridging between vesicles and the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously established that RBL cells expressing human a-syn variants serve as a versatile model for evaluating intracellular distributions of a-syn and accompanying effects on cell function that are mediated by its membrane interactions 1 , 31 . RBL cells have internal structures and activities resembling those in neurons, and by integrating fluorescence microscopy and functional assays, we showed this cell line to constitute an experimentally attractive system for developing hypotheses that can subsequently be tested in neurons and neuronal models more commonly associated with PD.…”
Section: Introductionmentioning
confidence: 99%